Shortage of Professional Science and Environmental Education Teachers in Nigeria - Olatunde Aiyedun; Ogunode Niyi Jacob (Asian Journal of Science Education, 2021)
This study evaluated the shortage of professional science and environmental education teachers in Nigeria’s educational institutions. The study used descriptive research survey design. The population of the study comprised of all public primary, secondary, and tertiary institutions in Nigeria. The sample size comprised of 600 science and environmental education students respectively made up of 200 pupils, 200 secondary students, and 200 tertiary students, selected randomly from six geopolitical zones of Nigeria. The research instrument used for data collection was a 18 structured questionnaire items rated on a 4-point Likert scale, with response options of Strongly Agree (SA); Agree (A); Disagree (D); and Strongly Disagree (SD).The responses of the respondents were presented in simple statistical table and analysed using Mean (x̅) and Grand Mean (gx̅). The findings revealed that problems of shortage of professional Science and Environmental Education teachers is common to the Nigerian educational institutions at all levels. Based on the result of findings, it was recommended that Environmental Education infused concepts in science subjects should be taught by qualified Environmental Education teachers and lecturers at all levels of education, beginning from the primary level to tertiary level in Nigeria.